2017
DOI: 10.1016/j.neuropharm.2017.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin in the medial prefrontal cortex attenuates anxiety: Anatomical and receptor specificity and mechanism of action

Abstract: Numerous studies in animals and humans have established that oxytocin (OT) reduces anxiety. In rats, the prelimbic (PL) subregion of the medial prefrontal cortex (mPFC) is among the brain areas implicated in the anxiolytic actions of OT. However, questions remain about the anatomical and receptor specificity of OT and its mechanism of action. Here we assessed whether the regulation of anxiety by mPFC OT is restricted to the PL subregion and evaluated whether oxytocin receptor (OTR) activation is required for O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 120 publications
(216 reference statements)
2
38
1
Order By: Relevance
“…By using an OTR antagonist, it has further been shown that endogenous OT has similar anxiolytic effects in the PL, as it has in the CeL (Nakajima et al 2014;Li et al 2016;Sabihi et al 2017). In addition, optogenetic and pharmacological activation of the OTR in the PL reduces anxiety-like behavior, in a genderdependent manner (Li et al 2016), further characterizing the differential role of different prefrontal-amygdala circuits during the modulation of fear memories in female and male rodents (Shansky et al 2010;Gruene et al 2015).…”
Section: Modulation Of Fear Circuits By Oxytocin In Preclinical Animamentioning
confidence: 95%
See 2 more Smart Citations
“…By using an OTR antagonist, it has further been shown that endogenous OT has similar anxiolytic effects in the PL, as it has in the CeL (Nakajima et al 2014;Li et al 2016;Sabihi et al 2017). In addition, optogenetic and pharmacological activation of the OTR in the PL reduces anxiety-like behavior, in a genderdependent manner (Li et al 2016), further characterizing the differential role of different prefrontal-amygdala circuits during the modulation of fear memories in female and male rodents (Shansky et al 2010;Gruene et al 2015).…”
Section: Modulation Of Fear Circuits By Oxytocin In Preclinical Animamentioning
confidence: 95%
“…Indeed, OTRsand OT-binding sites have been found in those circuits, especially in the ACC, PL, and CeL (Huber et al 2005;Nakajima et al 2014;Burkett et al 2016;Li et al 2016;Sabihi et al 2017) (Jiménez et al 2015), that together constitute the fear retrieval network. The OTRs are expressed specifically by GABAergic interneurons in all of the brain regions involved in fear retrieval (Huber et al 2005;Owen et al 2013;Nakajima et al 2014;Marlin et al 2015;Sabihi et al 2017). Importantly, OT-positive fibers originating from the PVN project to these areas (Knobloch et al 2012), and, at least in the CeL, OT is released from these fibers as observed following optogenetic stimulation and application of an OTR antagonist.…”
Section: Modulation Of Fear Circuits By Oxytocin In Preclinical Animamentioning
confidence: 99%
See 1 more Smart Citation
“…DA is involved in the experience of pleasure and has been implicated in multiple trauma-related pathologies such as depression [31] and substance use [32]. OT is known for its role in social bonding [78] but has been further implicated in depression [79], anxiety [80], and more recently in stress and related disorders [81, 82], marking its relevance for trauma-related psychopathology. Further studies have uncovered sex-related heterogeneity in the relationship of both OT and DA to trauma-related psychopathology.…”
Section: Direct Evidence Of Sex Differences In Trauma-related Psychopmentioning
confidence: 99%
“…If social interaction preferentially recruits IL-BLA projecting neurons, this could explain how activation of these cells regulates fear expression. Additionally, oxytocin is required for social buffering, and oxytocin signaling in the prelimbic cortex reduces anxiety [10,14,22,69,70]. One intriguing possibility is that oxytocin signaling directly or via connections from the mPFC recruits the subset of cells in the IL-PFC that are active during social interaction.…”
Section: Discussionmentioning
confidence: 99%